Experimental investigation on compressible flow over a circular cylinder at Reynolds number of between 1000 and 5000. (25th June 2020) - Nagata, T.; Noguchi, A.; Kusama, K.; Nonomura, T.; Komuro, A.; Ando, A.; Asai, K.
Abstract : Abstract : In the present study, a compressible low-Reynolds-number flow over a circular cylinder was investigated using a low-density wind tunnel with time-resolved schlieren visualizations and pressure and force measurements. The Reynolds number ( $Re$ ) based on freestream quantities and the diameter of a circular cylinder was set to be between 1000 and 5000, and the freestream Mach number ( $M$ ) between 0.1 and 0.5. As a result, we have clarified the effect of $M$ on the aerodynamic characteristics of flow over a circular cylinder at $Re=O(10^{3})$ . The results of the schlieren visualization showed that the trend of $M$ effect on the flow field, that are the release location of the Kármán vortices, the Strouhal number of vortex shedding and the maximum width of the recirculation, is changed at approximately $Re=3000$ . In addition, the spanwise phase difference of the surface pressure fluctuation was captured by the measurement using pressure-sensitive paint at approximately $Re=3000$ of higher- $M$ cases. The observed spanwise phase difference is considered to relate to the spanwise phase difference of the vortex shedding due to the oblique instability wave on the separated shear layer caused by the compressibility effects. The Strouhal number of the vortex shedding is influenced by $M$ and $Re$, and those effects are nonlinear. However, the effects of $M$ and $Re$ can approximately be characterized by the maximum width of the recirculation. In addition, the $M$ effect on the drag coefficient can be characterized by the maximum width of the recirculation region and the Prandtl–Glauert transformation.